Marination and fermentation of yellow mealworm larvae (Tenebrio molitor). (October 2018) - Borremans, A.; Lenaerts, S.; Crauwels, S.; Lievens, B.; Van Campenhout, L.
Abstract: The attractiveness of fresh edible insects might be enhanced by increasing their shelf life and taste. Two processes that have never been documented in the scientific literature for mealworms as such but that may achieve these goals are marination and fermentation. The objective of this study was to apply both processes on larvae of the yellow mealworm ( Tenebrio molitor ) and to monitor pH and microbial numbers during and after (for marination) the treatment. Blanched larvae were marinated for 6 days in either red wine or soy sauce. The total aerobic and spore counts increased with approximately 1 log cfu/g during marination, but during subsequent chilled storage for 17 days there was no microbial growth. Total viable counts were maximally 3.8 ± 0.1 log cfu/g for all samples. In contrast, a rapid increase of the total count to >7.0 log cfu/g was observed after 10–12 days for larvae that were only blanched. Therefore, marination can extend the shelf life for (at least) 7 days. Fermentation of crushed larvae with the starter Bactoferm F-LC and supplemented with 2.8% NaCl (w/w), 0.75% d (+)-glucose (w/w) and 0.015% NaNO2 (w/w) resulted in fast acidification and was effective inhibiting bacterial endospores and sulphite reducing clostridia. Highlights: Mealworms were marinated as well as fermented. Marination can result in a shelf life extension of at least 7 days. The behaviour of bacterial spores needs special attention during marinating. Fermentation of mealworms is possible when they are first crushed. Fermentation additives are necessary to control the unwanted background microbiota.